Prognostic relevance of the revised R status definition in pancreatic cancer: meta-analysis - Leonhardt, Carl-Stephan; Niesen, Willem; Kalkum, Eva; Klotz, Rosa; Hank, Thomas; Büchler, Markus W.; Strobel, Oliver; Probst, Pascal (BJS open, 2022)
The prognostic impact of margin status is reported with conflicting results after pancreatic cancer resection. While some studies validated an uninvolved resection margin (R0) 1 mm or more of tumour clearance, others have failed to show benefit. This systematic review and meta-analysis aimed to investigate the effects of margin definitions on median overall survival (OS).MEDLINE, Web of Science, and the Cochrane Central Register of Controlled Trials were searched for studies reporting associations between resection margins and OS between 2010 and 2021. Data regarding margin status (R0 circumferential resection margin (CRM) negative (CRM-), R0 CRM positive (CRM+), R0 direct, and R1 and OS were extracted. Hazard ratios (HRs) were pooled with a random-effects model. The risk of bias was evaluated with the Quality in Prognosis Studies (QUIPS) tool.The full texts of 774 studies were screened. In total, 21 studies compromising 6056 patients were included in the final synthesis. In total, 188 (24 per cent) studies were excluded due to missing margin definitions. The R0 (CRM+) rate was 50 per cent (95 per cent confidence interval (c.i.) 0.40 to 0.61) and the R0 (CRM−) rate was 38 per cent (95 per cent c.i. 0.29 to 0.47). R0 (CRM−) resection was independently associated with improved OS compared to combined R1 and R0 (CRM+; HR 1.36, 95 per cent c.i. 1.23 to 1.56).The revised R status was confirmed as an independent prognosticator compared to combined R0 (CRM+) and R1. The limited number of studies, non-standardized pathology protocols, and the varying number of margins assessed hamper comparability.
Gesehen am 12.05.2022